Basic & clinical pharmacology - Katzung, Bertram G. (New York, N.Y. : McGraw-Hill Education, 2018)
The fourteenth edition continues the extensive use of full-color illustrations and expanded coverage of transporters, pharmacogenomics, and new drugs of all types emphasized in prior editions. In addition, it reflects the major expansion of large-molecule drugs in the pharmacopeia, with numerous new monoclonal antibodies and other biologic agents. Case studies accompany most chapters, and answers to questions posed in the case studies appear at the end of each chapter. The book is designed to provide a comprehensive, authoritative, and readable pharmacology textbook for students in the health sciences. The book also offers special features that make it a useful reference for house officers and practicing clinicians.
Bibliogr. odkazy
Register
Keywords: farmakológia -- metódy; farmakológia klinická -- metódy; prípravky farmaceutické -- klasifikácia -- aplikácia a dávkovanie; kazuistiky; učebnica